Human Resource Management Practices for Teachers' Wellbeing - Ndidi , Loretta Okeke (International Journal of Educational Management, 2021)
Human resource management as an aspect of educational management focuses on the effective functioning of the organization. It covers areas such as staffing, staff maintenance, staff development, staff relations and retirement. The human factor is the key to the survival and success of any organization. Hence, their wellbeing should be of utmost concern to management. Teaching has been identified as one of the most stressful jobs, cases of depression, anxiety and stress among teachers abounds. This has affected the wellness and effectiveness of most teachers. There is need for human resource managers in schools to rivet attention on improving the wellbeing of teachers. This paper examined human resource management practices that enhances teachers' wellbeing. Some of the practices discussed are staff motivation, interpersonal communication skills, staff development, human relationship, involvement of teachers in decision making, laying emphasis on work- life balance and effective health campaign programs. The paper concluded that human resource management practices is key to fostering the general wellbeing of teachers in schools. The paper recommended that school managers should initiate effective health campaign programs in primary and secondary schools and continuous staff development programs on maintaining a balance between teachers' work and personal life.